2013
DOI: 10.3928/23258160-20131101-07
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Depth Imaging OCT and Indocyanine Green Angiography Changes in Acute Macular Neuroretinopathy

Abstract: The authors describe indocyanine green angiography (ICGA) and enhanced depth imaging optical coherence tomography (EDI-OCT) in a 46-year-old male patient with acute macular neuroretinopathy (AMN). The chief complaint was decreasing visual acuity and metamorphopsia in both eyes of 1-month duration. Visual field assessment, fluorescein angiography, OCT, ICGA, and EDI-OCT were performed initially and at 3 months. ICGA showed choroidal vascular hyperpermeability and punctuate choroidal hyperfluorescent spots, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…8 Compression and nonperfusion of small choroidal vessels caused by massive infiltration of inflammatory cells and stromal granulomas in the acute stage and shrinkage and dropout of the small choroidal vessels by the stromal scarring in the convalescent phase may contribute to the mechanism of this finding. 9 Similar findings were detected in our patient.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8 Compression and nonperfusion of small choroidal vessels caused by massive infiltration of inflammatory cells and stromal granulomas in the acute stage and shrinkage and dropout of the small choroidal vessels by the stromal scarring in the convalescent phase may contribute to the mechanism of this finding. 9 Similar findings were detected in our patient.…”
mentioning
confidence: 99%
“…However, few studies regarding morphology of the choroid in AMN patients have been reported. 8 We examined changes in morphology and circulation in the choroid of an AMN patient using enhanced-depth imaging OCT (EDI-OCT) and LSFG.An 11-year-old girl reported a paracentral scotoma of the right eye, first noted 3 months prior to presentation at our clinic. The patient's medical and family histories were unremarkable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the abnormal images of NIR imaging, AMN was considered to involve RPE. Sanjari et al [25] found the angiographic images of choroidal angiography showed enhanced permeability and prominentchoroid; the OCT images showed increased thickness of the choroid and irregular junction in the macular area, indicating that AMN lesions can involve the choroid. It is considered that the cause of AMN may come from the choroid, so it is recommended to classify it as choroidal disease.…”
Section: Acute Macular Neuroretinopathy Following Sars-cov-2 Infectionmentioning
confidence: 99%